Exploring gender differences in the internalization of religious values amongst the muslim Malaysian youth of the International Islamic University Malaysia, IIUM - Musazay, Maryam M. Saber (Institute of Education, International Islamic University Malaysia, 2011)
The purpose of this study is to explore religiosity amongst the Muslim Malaysian youth of the International Islamic University Malaysia IIUM. As such, the study examines the differences found in the internalization of religious values amongst the Muslim Malaysian youth of IIUM. In addition, the study also investigates the various ways that are utilized in the process of internalizing religious values amongst the Muslim Malaysian youth of IIUM. The study had adopted a quantitative approach and the sample was derived through convenience sampling. An adapted version of the Muslim-Religiosity Personality Inventory (MRPI) was used in the study for the data collection methodology. The study utilized both descriptive and inferential statistical tools to generate the findings. A pilot study was conducted in order to establish the validity and reliability of the adapted questionnaire. The study used SPSS version 17 for the purpose of data analysis. The findings of the study indicate that female students are slightly higher in terms of religious practice and “Ukhuwwa” spirit of brotherhood than the males at IIUM. As for the effects of western values on the youth; both male and female are influenced equally. This study is purely educational and applies to IIUM students and cannot be generalized throughout Malaysia due to the unique Islamic learning experience offered at IIUM. As such, it is recommended that future studies include and focus on the rest of the Malaysian population.